Towers for Offshore Wind Turbines - Kurian, V.J. (The 10th Asian International Conference on Fluid Machinery, 2009)
Increasing energy demand coupled with pollution free production of energy has found a viable solution in wind energy. Land based windmills have been utilized for power generation for more than two thousand years. In modern times wind generated power has become popular in many countries. Offshore wind turbines are being used in a number of countries to tap the energy from wind over the oceans and convert to electric energy. The advantages of offshore wind turbines as compared to land are that offshore winds flow at higher speed than onshore winds and the more available space. In some land based settings, for better efficiency, turbines are separated as much as 10 rotor diameters from each other. In offshore applications where only two wind directions are likely to predominate, the distances between the turbines arranged in a line can be shortened to as little as two or four rotor diameters. Today, more than a dozen offshore European wind facilities with turbine ratings of 450 kw to 3.6 MW exist offshore in very shallow waters of 5 to 12 m. Compared to onshore wind turbines, offshore wind turbines are bigger and the tower height in offshore are in the range of 60 to 80 m. The water depths in oceans where offshore turbines can be located are within 30 m. However as the distance from land increases, the costs of building and maintaining the turbines and transmitting the power back to shore also increase sharply. The objective of this paper is to review the parameters of design for the maximum efficiency of offshore wind turbines and to develop types offshore towers to support the wind turbines. The methodology of design of offshore towers to support the wind turbine would be given and the environmental loads for the design of the towers would be calculated for specific cases. The marine corrosion on the towers and the methods to control the corrosion also would be briefly presented. As the wind speeds tend to increase with distance from the shore, turbines build father offshore will be able to capture more wind energy. Currently two types of towers are considered. Cylindrical tubular structures and truss type structures. But truss type structures have less weight and flexibility in design. The construction of the offshore towers to harness the wind energy is also presented. The results will include the calculation of wind and wave forces on the tower and the design details for the tower.